Research on policy instruments for promoting green lifestyle in China—a multi-dimensional analysis based on current policy texts - Tian, Huawen; Cui, Yan; Dong, Jian (Frontiers in Environmental Science, 2024)
Introduction: In the past decade, the construction of ecological civilization has been a major national strategy in China. Since 2020, the Chinese government has officially proposed the goals of achieving peak carbon emissions by 2030 and carbon neutrality by 2060. As one of the key issues, promoting a green lifestyle is the fundamental means of achieving ecological civilization construction. It is an inevitable path to achieve the “carbon peak and carbon neutrality” goals. The current status of China’s efforts in this area is undoubtedly worth paying attention to. The purpose of this study is to analyze this issue. Method: This study uses text analysis methods. From 92 policy documents issued by the Chinese government, we extracted effective text totaling 100,122 characters for analysis. Perform three-level coding on the above text, and analyze the policy tools of the Chinese government to promote green lifestyles from three dimensions: the categories of policy tools, the target groups targeted by policy tools, and the implementing entities of policy tools. Conclusion: The study found that the current promotion of a green lifestyle in China primarily relies on information-based policy tools and market-based policy tools, with mandatory tools as a supplement. Information-based policy tools are mainly used for the public, while a combination of market-based policy tools, information-based policy tools, and mandatory policy tools is used for enterprises. Local governments’ attention to this issue is insufficient, manifested in the limited number of policy tools adopted, the single composition of these tools, and the lack of necessary constraints on enterprises. Discussion: Overall, the current policy tool selection is reasonable, but there are also problems such as over-reliance on information-based policy tools, overly simplistic market-based policy tools, insufficient market-based policy tools for the public, and the underuse of voluntary policy tools.